PELAKSANAAN SISTEM LPSE BERDASARKAN PERATURAN PRESIDEN NOMOR 54 TAHUN 2010 TENTANG PENGADAAN BARANG/JASA PEMERINTAH JO. PERATURAN LKPP NOMOR 1 TAHUN 2011 TENTANG TATA CARA E-TENDERING DALAM HUBUNGANNYA DENGAN PENGGUNAAN ANGGARAN YANG EFEKTIF DAN EFISIEN ( - ENDANG MASRONI,SH A.21212067, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2014)
AbstractThe development of science and technology in the field of information influences the law-making process in the procurement of goods / services and look for innovative solosi and to implement the above principles to form a legal product procurement of goods / services, as contained in Presidential Decree No. 54 of 2010, which utilize electronic means of informatics in conducting the procurement of goods / services of the government. In the process of auctions to procure goods and services from government to the provider of goods / services by the private sector (the public), and the system in this way by Presidential Decree No. 54 of 2010 which became one of the innovative legal products procurement of goods and other services, it Procurement embodied in electronic or E-Procurement,Procurement of Goods / Services as set out in Presidential Decree No. 54 Year 2010, (regulation. 54/2010), which is busy discussed among providers of Goods / Services. Is a concrete manifestation of the government's efforts to make prinsif Good Governace and clean Governnment, or a good governance and clean. "To implement the principle that the Government should implement the principle of accountability and the efficient management of resources, both rulemaking and does not take sides, as well as ensuring the economic and social interactions among relevant stakeholders in a transparent, professional and accountableImproving the quality of public services through good governance and clean, needs to be supported by effective financial management, efficient, transparent, and accountable. To improve the efficiency and effectiveness of the use of state finances is spent through PBJP, efforts are needed to create openness, transparency, accountability and fair competition principles in the process PBJP dbiayai by Budget / .APBD, in order to obtain goods / services that are affordable and quality and can dipertanggung justified both in terms of physical, financial, and government benefits for smooth functions and community service. Presidential Decree 54/2010 on Procurement of Goods / Services are intended to provide guidance regarding the procedures for setting PBJP simple, clear and konprehensip, as good governanceThe setting is based on Presidential Regulation No. 54 of 2010 is a rule to date, which is set in the procurement of goods / services of the government, but can the legal system that is owned by this Regulation answer all the challenges and goals of reform in the procurement of goods / services of the government to efficiency and effectiveness of the State Finance and Regional financial and if this setting when examined in substance is still commonKeyword: effective, efficient, transparent, and accountable